Directional amplification and ground motion polarization in Casamicciola area (Ischia volcanic island) after the 21 August 2017 Md 4.0 earthquake - Pischiutta, M.; Petrosino, S.; Nappi, R. (Frontiers in Earth Science, 2022)
In this paper we investigate ground motion directional amplification and horizontal polarization using ambient noise measurements performed in the Northern sector of Ischia Island which suffered relevant damage (VIII EMS) during the 21 August 2017, Md 4.0 earthquake. Over 70 temporary seismic stations were installed by the INGV EMERSITO task force, whose aim is to monitor site effects after damaging earthquakes in Italy. To investigate ground motion directional amplification effects, we have applied three different techniques, testing their performance: the HVSR calculation by rotating the two horizontal components; the covariance matrix analysis; time-frequency domain polarization analysis. These techniques resulted in coherent outcomes, highlighting the occurrence of directional amplification and polarization effects in two main sectors of the investigated area. Our results suggest an interesting pattern for ground motion polarization, that is mainly controlled by recent fault activity and hydrothermal fluids circulation that characterize the Northern sector of Ischia island.